UBA3 promotes the occurrence and metastasis of intrahepatic cholangiocarcinoma through MAPK signaling pathway - Zhang Huhu; Yang Jiahua; Song Qinghang; Ding Xiaoyan; Sun Fulin; Yang Lina (Acta Biochimica et Biophysica Sinica, 2024)
Intrahepatic cholangiocarcinoma (ICC) accounts for approximately 15% of primary liver cancers, and the incidence rate has been increasing in recent years. Surgical resection is the best treatment for ICC, but the 5-year survival rate is less than 30%. ICC signature genes are crucial for the early diagnosis of ICC, so it is especially important to identify signature genes. The aim of this study is to screen the signature genes of ICC and find the potential target for the treatment of ICC. We find that UBA3 is highly expressed in ICC, and knockdown of UBA3 inhibits ICC proliferation, invasion and migration. Mechanistic experiments show that UBA3 promotes ICC proliferation, invasion and migration by affecting ANXA2 through the MAPK signaling pathway. UBA3 is a target of bufalin, and bufalin targeting UBA3 inhibits ICC development and progression through the MAPK signaling pathway. In conclusion, our study shows that bufalin inhibits ICC by targeting UBA3, which has emerged as a new biomarker and potential therapeutic target for ICC.